2019
DOI: 10.1111/codi.14903
|View full text |Cite
|
Sign up to set email alerts
|

International evaluation of circumferential resection margins after rectal cancer resection: insights from the Swedish and Dutch audits

Abstract: Aim This study aimed to determine predictive factors for the circumferential resection margin (CRM) within two northern European countries with supposed similarity in providing rectal cancer care. Method Data for all patients undergoing rectal resection for clinical tumour node metastasis (TNM) stage I–III rectal cancer were extracted from the Swedish ColoRectal Cancer Registry and the Dutch ColoRectal Audit (2011–2015). Separate analyses were performed for cT1–3 and cT4 stage. Predictive factors for the CRM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In line with a previous collaborative project, we found that Dutch and Swedish patients had different patient-, tumour-, and surgical characteristics [8]. In addition, cTand cN-stages in colon cancer were more often defined by Swedish radiologists, despite the previously published unreliability of CT imaging for this purpose [48,49].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In line with a previous collaborative project, we found that Dutch and Swedish patients had different patient-, tumour-, and surgical characteristics [8]. In addition, cTand cN-stages in colon cancer were more often defined by Swedish radiologists, despite the previously published unreliability of CT imaging for this purpose [48,49].…”
Section: Discussionsupporting
confidence: 83%
“…Rectal cancer procedures were categorized as anterior resection with primary anastomosis with or without diverting stoma, Hartmann's procedure, and abdominoperineal excision (APE). For the evaluation of hospital volume, hospitals were categorized into low, low-intermediate, intermediate-high, and high volume hospitals, which was defined as < 30, 30-60, 61-90, and > 90 for colon cancer resections and < 12, 12-25, 26-50, > 50 for rectal cancer resection (as defined by Detering et al [8]).…”
Section: Data Extraction Outcomes and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of APR to restorative rectal resection was relatively high but comparable to recent population-based studies, with approximately one-third of all rectal cancer resections being APR. Incidence of APR for rectal cancer varies in the literature from 18% to 37% [3,[9][10][11][12]. Moreover, there have been reported instances of much higher APR rates in specific populations [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Detering et al . [4] used the colorectal cancer audits from Sweden and the Netherlands to examine factors associated with positive circumferential resection margins (CRM) over five years. CRM is chosen as a quality indicator; a negative margin indicates the achievement of curative resection, and it is associated with lower morbidity, mortality and improved post‐operative quality of life [4].…”
mentioning
confidence: 99%